UPAYA ISLAM DALAM MEMBENDUNG BUDAYA KORUPSI - Zainuddin Syarif (Institut Agama Islam Negeri Madura)
AbstractCorruption is one of chronic diseases in Indonesia. A country that has majority population of Islam has the highest population level. The causes are the bad character of state apparatus and the damage of political system and government That’s why Islam offers some solutions to solve corruption, such as proper salary, avoiding to receive a bribe and present, the counting of treasure in the first and the last of position period, a good model leader, equitable punishment and the most thing is the controlling from society.Kata-kata kunciKorupsi, koruptor, Islam, Sayyidina Umar bin al-Khattab